Marine biofilms on artificial surfaces: structure and dynamics. (19th July 2013) - Salta, Maria; Wharton, Julian A.; Blache, Yves; Stokes, Keith R.; Briand, Jean‐Francois
Summary: The search for new antifouling (AF) coatings that are environmentally benign has led to renewed interest in the ways that micro‐organisms colonize substrates in the marine environment. This review covers recently published research on the global species composition and dynamics of marine biofilms, consisting mainly of bacteria and diatoms found on man‐made surfaces including AF coatings. Marine biofilms directly interact with larger organisms (macrofoulers) during colonization processes; hence, recent literature on understanding the basis of the biofilm/macrofouling interactions is essential and will also be reviewed here. Overall, differences have been identified in species composition between biofilm and planktonic forms for both diatoms and bacteria at various exposure sites. In most studies, the underlying biofilm was found to induce larval and spore settlement of macrofoulers; however, issues such as reproducibility, differences in exposure sites and biofilm composition (natural multispecies vs. monospecific species) may influence the outcomes.